Análise espacial e temporal dos casos e contatos de hanseníase em município de alta endemicidade da Amazônia brasileira - Machado, Lúbia Maieles Gomes (2020)
Leprosy has a heterogeneous spatial distribution in Brazil, and maintains high endemicity in the state of Mato Grosso, including in the municipality of Alta Floresta. The identification of spatial clusters can show areas of greater risk of leprosy occurrence, contributing to the actions of epidemiological surveillance, an important component for controlling the endemic disease. Objective- To analyze the spatial and temporal distribution of new and registered leprosy cases and associated factors in Alta Floresta Mato Grosso, from 2016 to 2018. Method- This is an ecological-type epidemiological study, with a spatial and temporal approach to new cases and leprosy contacts in the city of Alta Floresta, Mato Grosso, in the years 2016 to 2018. Data were obtained through the Information on Notifiable Diseases (SINAN) and database of the PEP-HANS Brasil project, in addition to socioeconomic and environmental data obtained from the IBGE census. A description of the epidemiological profile of new cases and contacts was made. In the spatial analysis, the Bayesian Local Empirical method, Kernel analysis and SCAN spatial scanning were used. Factor analysis was performed to choose the socioeconomic variables of the IBGE, and subsequent analysis of spatial regression to investigate the factors involved with the existence of spatial patterns and clusters. MT. Results- In the period, 306 new leprosy cases were reported in Alta Floresta, with an average rate of general leprosy detection of 20.01 cases / 10,000 inhab., Being hyperendemic for the disease. Among the 2,167 listed contacts, 95.8% were examined in the period. The spatial distribution was heterogeneous in the municipality, with a higher concentration of cases and contacts evaluated in the northern region of the city over time, which suggests that contact surveillance can change the pattern of the disease and contribute to the reduction of areas risk. The areas assessed as most at risk are similar to those identified with higher detection rates and case density. The distribution of the disease was associated with poverty in the urban area. Conclusion - The present study proved to be an important tool to highlight critical areas for disease surveillance, in addition to show the effectiveness of contact tracing. Its use by the health management team is of great value to continuity to contacts tracing and increase other health surveillance actions.